The Design of Washer and Dryer Machine for Chopped Plastic Bottle - Kuni Nadliroh; Fatkhur Rohman (Universitas Muhammadiyah Sidoarjo, 2021)
Plastic bottle waste is a type of waste that is increasing in volume every day, this is due to the prevalence of bottled drinks being marketed, how can almost everyone produce one used plastic bottle a day, this results in more and more plastic bottle waste, if not immediately handled then it will be bad especially for the environment. Lately, collectors of plastic bottle waste have appeared but they do not immediately process the plastic bottle, so the selling price of used plastic bottle is cheap, to increase the selling value of used plastic bottles, the used plastic bottle are processed by chopping so that it increases the selling value of the plastic bottles. Here will be explained about the design of plastic bottle washers and dryers that can be operated with a sample capacity of 5 kg.